Superplasticity and forming of advanced materials - Tan, Ming Jen. (2008)
Superplasticity is the capability to deform crystalline solids in tension to unusually large plastic strains, often well in excess of 1000%. This phenomenon results from the ability of the material to resist localized deformation much the same as hot glass does. As high elongations are possible, complex contoured parts can be formed in a single press cycle often eliminating the need for multipart fabrications. This enables the designer to capture several detail parts into a one piece complex, formed structure. Thus materials with superplastic properties can be used to form complex components in shapes that are very near the final dimension. Superplastic forming also enhances design freedom, minimizes the amount of scrap produced, and reduces the need for machining. In addition, it reduces the amount of material used, thereby lowering overall material costs.